Process Distribution in the Network Systems - Augutis, J.; Ušpuras, E.; Krikštolaitis, R.; Matuzas, V. (Nonlinear Analysis: Modelling and Control, 2007)
Performing risk analysis of systems, evaluating reliability of technological objects, hazard of technological processes, we usually have to systems of network type and distribution of various processes in such systems. A well-known mathematical apparatus of diffusive processes example is dispersion in continuum medium (air, water, etc.). Process distribution in network systems is simpler, however, it much depends on network features. In this article theory of Markov chains is selected, distributions of different processes in transitional regimes are analysed as well as issues of their stability. Created models may be used in many different ways, for example, for the analysis or viruses in computer networks, hazard distribution in transport systems regarding transportation of hazardous materials, etc.
Keywords: distribution; process; network system